2023
DOI: 10.1021/acs.molpharmaceut.3c00039
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Scaffolds to Promote B cell Tolerance

Abstract: Autoimmune diseases are characterized by aberrant immune responses toward self-antigens. Current treatments lack specificity, promoting adverse effects by broadly suppressing the immune system. Therapies that specifically target the immune cells responsible for disease are a compelling strategy to mitigate adverse effects. Multivalent formats that display numerous binding epitopes off a single scaffold may enable selective immunomodulation by eliciting signals through pathways unique to the targeted immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 126 publications
(338 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies in materials science have demonstrated that for chimeric nanomaterials with a linear framework, bivalent or low-valency antigens often exhibit the ability to eliminate self-reactive B cells or antibodies, whereas high-valency antigens usually exhibit less efficacy [44][45][46][47]. We hypothesize that this is because both high-valency and bivalent antigens can trigger the same ADCC effects on B cells, but high-valency antigens induce a more robust Th-cell immunogenicity due to the higher peptide fragment concentrations presented during antigen presentation, resulting in an increase in the k4 value.…”
Section: The B Cells-targeted Adcc Effectmentioning
confidence: 99%
“…Numerous studies in materials science have demonstrated that for chimeric nanomaterials with a linear framework, bivalent or low-valency antigens often exhibit the ability to eliminate self-reactive B cells or antibodies, whereas high-valency antigens usually exhibit less efficacy [44][45][46][47]. We hypothesize that this is because both high-valency and bivalent antigens can trigger the same ADCC effects on B cells, but high-valency antigens induce a more robust Th-cell immunogenicity due to the higher peptide fragment concentrations presented during antigen presentation, resulting in an increase in the k4 value.…”
Section: The B Cells-targeted Adcc Effectmentioning
confidence: 99%